Ways of Benefiting From the Scientific Achievements of Muslims during the Abbasid Period - Sara Batool; Dr. Jawaad Haseeb (Journal of Religion and Society, 2025)
This research paper presents an in-depth exploration of the remarkable scientific progress made during the Abbasid Era (750–1258 CE) a period known as the golden age of Islamic civilization and compares it with the scientific advancements of the modern world. It begins by discussing the strong bond between Islam and science, showing how the Quran and the teachings of the Prophet ﷺ encourage the pursuit of knowledge and reflection upon the universe. This foundation reveals that Islam values knowledge not just for religious purposes but for the overall betterment of humanity. The second section introduces the Abbasid Caliphate, highlighting the rule of its 37 caliphs, their styles of governance, and their notable efforts in promoting science and education. This part emphasizes how Abbasid rulers supported scholars and helped establish Baghdad as a leading global hub of knowledge. The third section details the groundbreaking scientific contributions of Muslim scholars during the Abbasid period in fields such as medicine, astronomy, physics, chemistry, and mathematics. It also includes the names of renowned scientists, their inventions, and the enduring impact of their work on global intellectual traditions. The final section draws a comparison between Abbasid and contemporary scientific progress, showing how the methods and spirit of inquiry developed in the Abbasid age laid the groundwork for today’s research and innovation. This analysis reinforces the idea that Islamic civilization didn’t merely preserve ancient knowledge but also expanded it, setting the stage for continued scientific growth. Keywords: Scientific Achievements, Muslims. Abbasid Period, Innovation, Humanity